A building bio-climatic design tool incorporating passive strategies in residential dwellings design of composite climate of India. (16th November 2021) - Kumar, Sanjay; Mathur, Anuj; Rana, K.B.; Kumar, Chandan
The objective of the present work is to assess the potential of different passive design strategies using the bio-climatic approach in residential spaces across the composite climate in India. For this purpose, a modified building bio-climatic design chart based on composite climate specific adaptive thermal comfort zone (CZ) has been used. The climates of four major cities namely Delhi, Jaipur, Lucknow, and Hyderabad, have been selected for bio-climatic analysis using typical meteorological year (TMY) data. The results from the bio-climatic analysis showed that comfort can vary 30% to 60% of the total time during summer and 43% to 70% of the total time during the winter season, respectively. During warmer half of the year (March-October) natural ventilation, sun shading, and direct evaporative cooling proved to be the better choice for passive cooling. However, passive solar heating only provides the noticeable result for improving indoor comfort conditions during the colder half of the year (November-February) for all selected cities. Finally, this study put forward a guideline matrix for the use of passive design schemes in buildings for composite climate of India.